Formación docente previo al servicio en el cantón Latacunga - Yanchaguano Llumiquinga, Rosa María (2017)
The aim of the present research was to gather information on the current reality of pre-service teacher education, it was investigated the problem of how and how teachers are trained today; For example, it was verified whether the current teacher education is adjusted to the needs of the country, or whether the changes that have occurred in the teaching career have been favorable or detrimental. For this, a field investigation was carried out, and the methods used in this research were the deductive method that was used for the elaboration of the citations in the technical scientific basis; the analytical method, this was used in the development of the tabulation; the synthetic method, was used in the design of the conclusions and recommendations. On the other hand, this research project contributed elementary information on pre-service teacher training; to the project that will develop the career of Sciences of the Education mention Basic Education, of the Technical University of Cotopaxi, which belongs to the parish Eloy Alfaro of the Latacunga canton, province of Cotopaxi....